Homotopic connectivity in drug-naïve, first-episode, early-onset schizophrenia - Li, Hui-Jie (J Child Psychol Psychiatry, 2014)
BACKGROUND: The disconnection hypothesis of schizophrenia has been extensively tested in adults. Recent studies have reported the presence of brain disconnection in younger patients, adding evidence to support the neurodevelopmental hypothesis of schizophrenia. Because of drug confounds in chronic and medicated patients, it has been extremely challenging for researchers to directly investigate abnormalities in the development of connectivity and their role in the pathophysiology of schizophrenia. The present study aimed to examine functional homotopy – a measure of interhemispheric connection – and its relevance to clinical symptoms in first-episode drug-naïve early-onset schizophrenia (EOS) patients. METHODS: Resting-state functional magnetic resonance imaging was performed in 26 first-episode drug-naïve EOS patients (age: 14.5 ± 1.94, 13 males) and 25 matched typically developing controls (TDCs) (age: 14.4 ± 2.97, 13 males). We were mainly concerned with the functional connectivity between any pair of symmetric inter-hemispheric voxels (i.e., functional homotopy) measured by voxel-mirrored homotopic connectivity (VMHC). RESULTS: EOS patients exhibited both global and regional VMHC reductions in comparison with TDCs. Reduced VMHC values were observed within the superior temporal cortex and postcentral gyrus. These interhemispheric synchronization deficits were negatively correlated with negative symptom of the Positive and Negative Syndrome Scale. Moreover, regions of interest analyses based on left and right clusters of temporal cortex and postcentral gyrus revealed abnormal heterotopic connectivity in EOS patients. CONCLUSIONS: Our findings provide novel neurodevelopmental evidence for the disconnection hypothesis of schizophrenia and suggest that these alterations occur early in the course of the disease and are independent of medication status.